El Excentrico, 1953-07-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
July 5, 1953, [5 de julio de 1953]. Anos 3, No, 17. Cover has a photos taken at the Lab Ameteur Contest with headline, "Triunfadores del Concurso de Aficionados Lab. D'Franssia." (transl: Winners of the Lab Ameteur Contest. D'Franssia).